Pediculosis among the children of different social status in Dhaka (Bangladesh Journal of Zoology, 2013)
The prevalence of head lice (Pediculus humanus capitis) infestation was studied among the children (1 to 7 years) in the area of Mirpur Bihari Camp, Mirpur-11, Dhaka. A total of 300 children was examined from February 2011 to January 2012 and 59.67% prevalence of head lice infestation was observed. The prevalence of pediculosis was significantly higher (p